A Texas Soldier's Christmas - Thacker, Cathy Gillen (Thacker, Cathy Gillen. Texas legacies. Lockharts., 2017)
Just the sight of United States Army Lieutenant Zane Lockhart makes nurse Nora Caldwell (and every other woman he meets) weak at the knees. But Nora has to keep a level head this time. As tempting as it is to fall into his finely sculpted arms--again--she's got her beautiful baby boy, Liam, to think of now. She can't settle for some temporary loving. She and her son need, and deserve, more. Zane has always responded to the call of duty. But that dedication has meant saying goodbye to Nora far too often. He can't blame her for doubting that he's finally ready to put her--and Liam--first. Can the Christmas gift of a lifetime convince her?